Circular RNA 103862 Promotes Proliferation and Invasion of Laryngeal Squamous Cell Carcinoma Cells Through the miR-493-5p/GOLM1 Axis - Wang, Xin; Wu, Tianyi; Wang, Peng; Yang, Like; Li, Qiuying; Wang, Jingting; Zhao, Rui; Zhang, Jiarui; Liu, Ming; Cao, Jing; Tian, Linli; Yu, Boyu; et al. (Frontiers in Oncology, 2020)
Extensive studies suggest that circRNAs can be a key contributor to oncogenesis. Yet, the function of circRNAs in laryngeal squamous cell carcinoma (LSCC) is not clear. Primarily, we examined the function of circRNA_103862 in LSCC progression, by analyzing the tissue specimens collected from patient with LSCC; and by using different LSCC cell models in vitro, and a LSCC xenograft model in nude mice. We found that circRNA_103862 was frequently up-regulated in the tissues of LSCC and was correlated with matastasis and prognosis of LSCC patients. Furthermore, in vitro and in vivo experiments data suggested that circRNA_103862 downregulation could reduce proliferation, migration and invasion ability of LSCC cells. In terms of mechanism exploration, miR-493-5p was sponged by circRNA_103862. Rescue experiments also showed that circRNA_103862 could achieve carcinogenic effect by regulating miR-493-5p. Moreover, a luciferase reporter analysis showed that Golgi membrane protein 1 (GOLM1) is a downstream effector of miR-493-5p. In conclusion, our data suggested that circRNA_103862 promotes the proliferation of LSCC through targeting the miR-493-5p/GOLM1 axis, and it might serve as a potential prognosis marker and therapy target for LSCC.